CONSUMER-EXPERT INTERACTION IN PRODUCT CHOICES: REVOLUTIONIZING CONSUMER DYNAMICS WITH AUTONOMOUS EXPERTS IN A MULTIDISCIPLINARY FRAMEWORK - Dahiwal, Rushikesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Consumer dynamics, encompassing preferences, behaviors, and decision-making processes, have grown increasingly intricate within today’s diverse and choice-saturated markets. Autonomous experts—whether human, AI-powered, or hybrid—have emerged as influential facilitators, transforming consumer interactions by offering impartial, empathetic, and technology-enhanced guidance. These experts empower consumers to make informed choices with greater clarity, confidence, and satisfaction. This study presents a multidisciplinary framework that investigates the critical role autonomous experts play in reshaping consumer decision-making. Incorporating insights from psychology, behavioral economics, marketing, communication studies, and technology, the framework demonstrates how these experts build trust, counteract cognitive biases, and facilitate personalized yet unbiased decisions. By analyzing key interaction stages—such as trust development, needs evaluation, and post-purchase support—the study illustrates how autonomous experts influence and adapt to evolving consumer behaviors. To bridge theoretical insights with practical applications, the paper examines their role in sectors like retail, healthcare, and financial services, focusing on their ability to address challenges such as decision fatigue, inclusivity, and ethical data practices. By proposing actionable strategies and tackling ethical considerations, this research highlights the transformative potential of autonomous experts and offers a strategic roadmap for revolutionizing consumer engagement.